THE NEED FOR A TARGETED APPROACH TO THE DEVELOPMENT OF THE ARCTIC - N. Komkov; V. Sutyagin; N. Volodina (Модернизация, инновация, развитие, 2016)
The intensive development of the adjacent Arctic zone of Russia (ASR) is connected with the necessity of the use of information and logical model. Effi cient organization of the process of development requires, first of all, the comprehensive development of all areas of transport: air, sea, rail, road, pipeline and is based on the solution of complex engineering problems encountered in exploration and development of mineral deposits and transportation of refi ned products in arctic conditions.